Bacterial Load and Antimicrobial Profile of Escherichia coli and Listeria spp. Isolates from Muscle Tissues of Slaughtered Cattle at a Major Abattoir in Ibadan, South-Western Nigeria - Victoria O. Adetunji; Hezekiah K. Adesokan; Charity A. Agada; Tajudeen O. Isola (Journal of Basic & Applied Sciences, 2014)
Meat is prone to contamination by pathogenic organisms during slaughter and processing due to unhygienic practices in Nigeria. In recent times, there has been an increase in the prevalence of antibiotic resistant foodborne pathogens due to increased drug misuse in livestock industry. We assessed the level of microbial contamination of fresh muscle tissues from cattle slaughtered in a major abattoir in Ibadan immediately after slaughter and also determined the antibiogram of Escherichia coli and Listeria spp isolates from the muscle tissues. These were done using standard plate and Bauer-Kirby disc diffusion techniques for bacteriological assay and antibiotic sensitivity testing, respectively. We found that the muscle tissues from the slaughtered cattle were highly contaminated, with the Total Aerobic (6.59±0.94 log cfu/g), coliform (6.43±0.67 log cfu/g) and Listeria (6.96±0.32 log cfu/g) counts being higher than the acceptable international standards. Isolated E. coli and Listeria spp demonstrated 100% resistance to all tested antibiotics. We thus recommend further studies to be carried out on the molecular characteristics of antibiotic resistant genes responsible for transferability of bacterial resistance among foodborne pathogens in Nigeria.